Relationship between gamma-glutamyl transferase/albumin ratio and coronary slow flow phenomenon - Uğur Küçük; Kadir Arslan (National Scientific Medical Center, 2022)
Aim: The coronary slow flow phenomenon (CSFP) is a pathology characterized by decreased coronary flow without stenosis on angiographic imaging. It is known that gamma-glutamyl transferase (GGT) and albumin play a role in cardiovascular disease. Our aim was to investigate whether GGT-to-albumin ratio could predict CSFP. Material and methods: Our cross-sectional study included 149 patients who had myocardial ischemia and underwent coronary angiography in our clinic. Our study consisted of two groups, with and without CSFP. The GGT-to-albumin ratio values were compared between the groups, and the presence of a risk factor for CSFP was evaluated with a regression analysis. Results: A statistical significance was observed between the groups with and without CSFP in terms of GGT-to-albumin ratio values, (6.16 and 4.46, respectively; p<0.001). There was a moderate correlation between GGT-to-albumin ratio and the mean thrombolysis in myocardial infarction frame counts (r=0.423, p<0.001). In the univariate logistic regression analysis revealed that GGT-to-albumin ratio was predictive of CSFP [odds ratio: 0.460, 95% confidence interval (CI): 0.341-0.620, p<0.001]. In the receiver operating characteristic curve analysis performed on GAR to distinguish CSFP, the GGT-to-albumin ratio exhibited 84% sensitivity and 59% specificity for values ≥4.67 (area under the curve: 0.78, 95% CI: 0.708-0.859, p<0.001). Conclusion: GGT-to-albumin ratio values were found to increase in the presence of CSFP. Our findings advise that GGT-to-albumin ratio might also play a function inside the pathogenesis of CSFP.